2020
DOI: 10.1002/er.6221
|View full text |Cite
|
Sign up to set email alerts
|

Early development of a shaftless horizontal axis wind turbine for generating electricity from air discharged from ventilation systems

Abstract: The air discharged from ventilation systems is a high potential wind resource for generating electricity in countries where wind speed is unreliable or weak, such as in Thailand. The air discharged from ventilation systems produces consistent and high-speed wind when benchmarked against natural wind. However, the limitations of conventional wind turbines are that they have negative impacts on the ventilation system and are inconvenient to install in many areas. The innovative shaftless horizontal axis wind tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Locating the turbine at a high point in the duct can cause the back force to reduce significantly. In the research by Wachira Puttichaem et al [100,101], the researchers suggested an efficiency of 51%, which is close to the Betz limit. From this, it is clear that housing such SSHWT within an augmentation device would increase its efficiency exponentially.…”
Section: Wind Turbine Efficiency Against the Betz Limitmentioning
confidence: 75%
See 2 more Smart Citations
“…Locating the turbine at a high point in the duct can cause the back force to reduce significantly. In the research by Wachira Puttichaem et al [100,101], the researchers suggested an efficiency of 51%, which is close to the Betz limit. From this, it is clear that housing such SSHWT within an augmentation device would increase its efficiency exponentially.…”
Section: Wind Turbine Efficiency Against the Betz Limitmentioning
confidence: 75%
“…Even though this was taken care of by employing the second VAWT, the wastage of exhaust wind is still not addressed. Similarly, the design suggested by Wachira Puttichaem et al [100] has the same issue of wind wastage through the centermost region. Although researchers may argue the benefits of the SSWT in terms of reducing the negative impact on the base system, a careful study would show that the efficiency is barely at 51%.…”
Section: Latest Trends In the Development Of Kinetic Energy Recovery ...mentioning
confidence: 90%
See 1 more Smart Citation
“…Velocity inlet (u=1 m/s) is adopted at the entrance of the calculation domain, pressure outlet is adopted at the exit, velocity inlet or slip wall is adopted at the drainage basin wall (u=1 m/s), and the no-slip wall is adopted at the diversion cover wall [7] . The SSTkíw turbulence model is selected, the Segregated implicit solver is used, the pressure-velocity coupling is determined by the SIMPLE algorithm, and the gradient is determined by the GreenGausenode-based method.…”
Section: Simulation and Comparison Of The Speed Increase Effect Of Th...mentioning
confidence: 99%
“…Wind energy, light energy, mechanical energy, and other environmental energy sources widely exist in cities [ 8 , 9 ]. Among them, wind energy has many advantages, such as its wide distribution in all-weather situations and ease of harvesting [ 10 , 11 ]. Average wind speeds in cities are generally 1.2 m/s to 3.8 m/s in Chinese cities from the National Centers for Environmental Information (NCEI).…”
Section: Introductionmentioning
confidence: 99%